Pengaruh Media Pembelajaran Berbasis Canva terhadap Minat Belajar IPAS Siswa Kelas V SDN 04 Bengkayang - Egi, Fransiskus; Damas Sadewo, Yosua (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of Canva-based learning media on the science and social studies (IPAS) learning interest of fifth-grade students at SDN 04 Bengkayang. The study was motivated by students' low learning interest, as indicated by limited attention, interest, enthusiasm, and participation during classroom learning. A quantitative approach with a One Group Pretest-Posttest experimental design was employed. The participants consisted of 34 fifth-grade students. Data were collected through questionnaires and documentation and analyzed using validity, reliability, normality, and hypothesis testing with the Paired Sample t-Test in SPSS. The results showed that the research instrument was valid and reliable. The normality test yielded a significance value of 0.118 (>0.05), indicating that the data were normally distributed. The hypothesis test produced a Sig. (2-tailed) value of 0.000 (<0.05), indicating a significant effect of Canva-based learning media on students' learning interest. The mean pretest score increased from 51 to 67 in the posttest. It can be concluded that Canva-based learning media has a significant positive effect on the IPAS learning interest of fifth-grade students at SDN 04 Bengkayang.